CA-125 and Ceruloplasmin Levels in Ovarian Cancer Patients - Mangala Hegde; Yousef Rezaei Chianeh; Jeevan Shetty; Donald J. Fernandes; Pragna Rao (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: The initial stage of proliferation of epithelial ovarian carcinoma (EOCa) is usually asymptomatic. Due to the lack of sensitive and reliable markers in majority of patients the disease is widespread at the time of diagnosis. The reliable serum biomarkers currently accepted is CA125 but there is limitation in case of sensitivity of CA125 as it is detectable only in 50% of patients in stage I and 80% of patients with advanced stage. We have investigated a correlation between serum CA125 and ceruloplasmin (as a marker of angiogenesis) in ovarian cancer in pre-treatment and post-treatment patients, compared with controls and found to be a significant marker for diagnosis. Material and Methods: A study was done in age group between 18-45 years diagnosed with ovarian cancer. (cases: n=50, controls: n=50). Cancer was diagnosed based on biopsy and histopathological examination. Serum Ceruloplasmin and CA 125 were estimated in pre-treatment and post-treatment patients and statistically significant decrease of these biomarkers observed in post treatment when compared with pre treatment patients. Result: We found that serum CA 125 to ceruloplasmin ratio was moderately increased in pre-treatment ovarian cancer patient. The serum ceruloplasmin (p<0.0001) level was significantly increased in ovarian cancer patients as compared to controls. Conclusion: Serum ceruloplasmin as well CA-125 level decline after treatment, and have been associated with efficacy and safety of novel therapeutic strategy to improve diagnosis and treatment for cancer. [Cukurova Med J 2015; 40(3.000): 510-516]